On the capacity of MISO FSO systems over gamma-gamma and misalignment fading channels. - Boluda-Ruiz, Rubén; García-Zambrana, Antonio; Del Castillo Vázquez, Beatriz; Del Castillo Vázquez, Carmen (Optica Publishing Group, 2015)
In this work, the ergodic capacity performance for multipleinput/single-output (MISO) free-space optical (FSO) communications system with equal gain combining (EGC) reception is analyzed over gamma-gamma and misalignment fading channels, which are modeled as statistically independent, but not necessarily identically distributed (i.n.i.d.). Novel and analytical closed-form ergodic capacity expression is obtained in terms of H-Fox function by using the well-known inequality between arithmetic and geometric mean of positive random variables (RV) in order to obtain an approximate closed-form expression of the distribution of the sum of M gamma-gamma with pointing errors variates. In addition, we present an asymptotic ergodic capacity expression at high signal-to-noise ratio (SNR) for the ergodic capacity of MISO FSO systems. It can be concluded that the use of MISO technique can significantly reduce the effect of the atmospheric turbulence as well as pointing errors and, hence, provide significant capacity gain over the direct path link (DL). The impact of pointing errors on the MISO FSO system is also analyzed, which only depends on the number of laser sources and pointing error parameters. Moreover, it can be also concluded that the ergodic capacity performance is dramatically reduced as a consequence of the severity of pointing error effects. Simulation results are further demonstrated to confirm the analytical results
https://openpolicyfinder.jisc.ac.uk/id/publication/13361
Keywords: Comunicaciones ópticas; Atmospheric turbulence; Free-space optical communication; Optical communications